2022
DOI: 10.3390/rs14030604
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Cloud-to-Ground Lightning Nowcasting with Multisource Data Based on a Video Prediction Method

Abstract: The evolution of lightning generation and extinction is a nonlinear and complex process, and the nowcasting results based on extrapolation and numerical models largely differ from the real situation. In this study, a multiple-input and multiple-output lightning nowcasting model, namely Convolutional Long- and Short-Term Memory Lightning Forecast Net (CLSTM-LFN), is constructed to improve the lightning nowcasting results from 0 to 3 h based on video prediction methods in deep learning. The input variables to CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The first 12 hr of each simulation are considered the spin‐up time, which is consistent with recent similar studies conducted by Guo et al. (2022) and Federico et al. (2022).…”
Section: Case Studies and Methodologysupporting
confidence: 69%
See 1 more Smart Citation
“…The first 12 hr of each simulation are considered the spin‐up time, which is consistent with recent similar studies conducted by Guo et al. (2022) and Federico et al. (2022).…”
Section: Case Studies and Methodologysupporting
confidence: 69%
“…The first 12 hr of each simulation are considered the spin-up time, which is consistent with recent similar studies conducted by Guo et al (2022) and Federico et al (2022). Table 2 summarizes the model configurations and physical parameterizations, the selection of which is based on previous studies (e.g., Gharaylou et al, 2019;Yair et al, 2010).…”
Section: The Wrf Modelmentioning
confidence: 92%
“…We thus choose three periods with relatively high lightning flash counts scattered in January 2013 (4-6 January), 2015 (25-29 January), and 2018 (28-31 January) as the cases for WRF-Chem simulation (figure 1(d)). We follow previous studies (Federico et al 2014, Gharaylou et al 2020, Guo et al 2022 to set the first 12 h in each simulation for spin-up to allow the meteorological conditions to be adjusted to different scenarios.…”
Section: Wrf-chem Model Simulationmentioning
confidence: 99%
“…It can be very destructive as a result of intense rainfall that occurs over short periods and often results in flash floods. Many studies showed that the cloud-to-ground lightning flash activities of a thunderstorm could be used in local short term forecasting of heavy rain or precipitation estimation and flash flood or hailstone [11]- [14]. Thus, high precipitation corresponds to strong atmospheric activity in convective systems.…”
Section: Introductionmentioning
confidence: 99%